THE EXPERIENCE OF BUILDING JUVENILE JUSTICE IN CANADA AND IT’S ROLE FOR UKRAINE - Хмелевська, Н.В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2021)
Abstract. The article is devoted to researching the experience of building juvenile justice in Canada and analyzing it’s role in the development of juvenile justice in Ukraine. Today, our state is actively building a system of juvenile justice and borrowing the experience of states that have been creating child-friendly justice for many decades, and the Ukrainian system will need it very much. Studying the best world practices will make it possible to improve one’s own system, and Canada is one of the countries that has created effective juvenile justice. Thus, the purpose of the article is to analyze the history of the formation of juvenile justice in Canada and its role for Ukraine. The article concludes that Canada’s juvenile justice system has many years of experience, during which norms that work best in the field of juvenile justice have been tested. In Canada, there is no «punitive» approach to juvenile offenders. Such a system found its manifestation in Ukraine and continues to develop. In Canada, significant attention is paid to the prevention of juvenile delinquency, which helps to reduce the crime rate. Ukraine also pays attention to this, but not at a sufficient level, so this aspect needs additional regulation by developing effective mechanisms for the prevention of crime among minors. The Canadian experience shows that it is necessary to pay attention not only to the juvenile offender, but also to the victims and witnesses who are participants in criminal proceedings. In Ukraine, insufficient attention is paid to this issue, but development in this area is necessary for restorative justice.

Анотація. Стаття присвячена дослідженню досвіду побудови ювенальної юстиції Канади та аналізу його ролі для становлення ювенальної юстиції в Україні. Сьогодні наша держава активно будує систему ювенальної юстиції та запозичує досвід держав, які протягом багатьох десятиліть формують правосуддя дружнє до дитини і це дуже знадобиться українській системі. Вивчення кращих світових практик зробить можливим покращити власну систему, а Канада є однією з держав, де створена дієва ювенальна юстиція. Таким чином, метою статті є аналіз історії становлення ювенальної юстиції Канади та його роль для України. У статті зроблені висновки про те, що ювенальна юстиція Канади має багаторічний досвід, протягом якого були апробовані норми, які найкраще працюють у сфері ювенальної юстиції. У Канаді відсутній «каральний» підхід до неповнолітніх, які вчинили кримінальні правопорушення. Така система знайшла свій прояв і в Україні та продовжує розвиватись. Значна увага в Канаді приділяється попередженню вчинення кримінальних правопорушень неповнолітніми, що допомагає знизити рівень злочинності. В Україні теж приділяють цьому увагу, однак не на достатньому рівні, тому цей аспект потребує додаткового врегулювання шляхом розроблення дієвих механізмів попередження злочинності серед неповнолітніх. Канадський досвід показує, що необхідно також звертати увагу не лише на неповнолітнього правопорушника, але й на потерпілих та свідків, які є учасниками кримінального провадження. В Україні приділяється недостатня увага цьому питанню, однак розвиток в цій сфері є необхідним для відновного правосуддя.
Досвід побудови ювенальної юстиції Канади та його роль для України
Keywords: juvenile justice; restorative justice; history of juvenile justice development; child-friendly justice; ювенальна юстиція; неповнолітні; відновне правосуддя; історія розвитку ювенальної юстиції; правосуддя дружнє до дитини